HIDROLISIS RUMPUT LAUT (Glacilaria sp.) MENGGUNAKAN KATALIS ENZIM DAN ASAM UNTUK PEMBUATAN BIOETANOL - Armawan Sandi, Yohanes; Susanah Rita, Wiwik; Ciawi, Yenni (Jurnal Kimia (Journal of Chemistry); Vol. 10, No. 1 Januari 2016, 2016)
The aim of this research is to determine the effect of enzyme and acids concentration on the yield of glucose produced in the hydrolysis of Glacilaria sp. in the production of bioethanol. The concentrations of cellulase used were 200 units/mL, 400 units/mL, 600 units/mL, 800 units/mL and the concentration of sulphuric acid (H 2 SO 4 ) and hydrochloric acid (HCl) used were 1%, 3%, 5%, 7% (w/v). The concentration of reduction sugar was determined using Anthrone and analyzed using UV-Vis spectrophotometry and the determination of ethanol concentration was carried out by using gas chromatography. The results showed that the contents of reducing sugar produced by sulphuric acid (H 2 SO 4 ) hydrolysis were 26,19%; 36,69%; 41,40%; 45,0% (v/v), by hydrochloric acid (HCl) were 12,12%; 14,03%; 15,17%; 16,50% (v/v), and by cellulase enzyme were 46,15%; 46,73%; 47,68%; 48,25% (v/v). Optimum concentration of reducing sugar produced by hydrolysis using 800 units/mL cellulase was 48,25% (v/v). The optimum length of fermentation to produce bioethanol using Glacilaria sp. as raw material was 5 days. In the fermentation, inoculum with a concentrations of 5% and 10% (w/v) produced 0,85% and 1,51% (v/v) ethanol.
Keywords: Gracilaria sp., cellulase, H2SO4 and HCl, fermentation, bioethanol